Plan de marketing para la empresa Pctronic de la ciudad de Nueva Loja, cantón Lago Agrio, provincia de Sucumbíos, para el año 2017 - Caiza Herrera, Ruth Viviana (2017)
The present investigation was carried out with the objective of elaborating a marketing plan for the company PC TRONIC of the city of Nueva Loja, Canton Lago Agrio, Province of Sucumbíos, in the period 2017, that allows to position the products in the local market and increase the publicity and dissemination of the products offered. The research was supported by the use of the deductive, inductive, analytical and statistical method, also an observation sheet, an interview with the manager, surveys directed to the 331 external clients and the 9 internal clients, so that information was vital Importance that allowed to analyze internally the company and to determine with exactitude its existing strengths and weaknesses in its structure and operation. The analysis of the external analysis was carried out, which was supported by the analysis of Porter's five forces and the Pest analysis, which allowed us to establish the main opportunities and threats. The most important results of the research were the weighting of the matrix of evaluation of external factors that reached a value of 3.05 the total weighted value of internal factors was 2.90, which could establish that in The external environment the opportunities are greater than the threats. And in the inner environment, there is a predominance of strengths over weaknesses. However, it is necessary to identify strategies that help mitigate possible risks for PCTRONIC. On the basis of the SWOT analysis, the realization of the high-impact valuation matrix was established, through which the strategic objectives were established, detailing the problem, goal, strategy, policy, tactics, activities, responsibility, time and Budget of the materialization of the marketing plan. The strategic objectives proposed for the proposed marketing plan are; 1. Position the company PCTRONIC in the minds of consumers, 2. Strengthen the knowledge of the sales staff with new methods in customer service, 3. Increase the client portfolio for the company PCTRONIC, 4. Disseminate massively in the local market The offer of The different products and services of PCTRONIC, resulting in a total budget of $ 17,800.00 that is required to carry out the marketing plan for the lapse of 1 year. Finally, it was concluded that there was no marketing plan in the company "PC TRONIC", as well as a business philosophy in which the business image clearly shows, suffering from strategies and a limited diffusion of the products offered.